TADRIS MAHARAH AL-KALAM FI MADRASAH TSUNAIYYAH AL-LUGHAH AL-STANAWIYAH - Nasution, Sahkholid (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2015)
Giving the name Bilingual of the Madrasah Aliyah Bilingual Batu this a characteristic of this madrasah among madrasah-madrasah aliyah especially in Batu City. Bilingual in question is the use of the Arabic language and English as the language of instruction in these madrasah. Pay attention to the peculiarities of the madrasah, the writer wanted to dig further information about the development process of learning the Arabic language at the school, especially in the field of speaking skills (Maharah Kalam). Therefore, the approach used in writing this article is a qualitative approach with descriptive - evaluative method. It can be concluded that in general the process of the development of the Arabic language at the school has been following the principles of the development of the Arabic language to non-Arabs, but there are still many shortcomings and problems were found, including the media, environment and human resources are inadequate.